Inventory and quantitative assessment of geosites in Rabat-Tiflet Region (North Western Morocco): Preliminary study to evaluate the potential of the area to become a geopark - Mehdioui, Sakina (2020)
The Rabat-Tiflet area (north-western Morocco) has a complex geological setting and a high geodiversity, two reasons that justify the geoheritage inventory done in this work. The inventoried 13 geosites were quantitatively assessed and clearly show that the Tortonian/Messinian Akrech River GSSP Stratotype is the most important geosite in the area due to its high international scientific value. In addition, the majority of the other geosites are characterized by moderate scientific, educational, and touristic values and high degradation risk. Therefore, a geoconservation strategy should be implemented in this area by national and local authorities to protect and conserve this geological heritage. This study may help the development of a new geopark project in Morocco, a country where the geopark concept is still emerging.